2019
DOI: 10.12659/msm.914234
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Obstetric Hemorrhage with Fibrinogen Concentrate

Abstract: BackgroundPostpartum hemorrhage (PPH) is related to several factors but is frequently associated with coagulopathy with maternal mortality. Fibrinogen is a very important agent for bleeding. When its concentration is decreased, severe surgical blood loss may occur. Here, we investigate the association of postpartum bleeding characteristics with evolution of PPH in patients who were taking fibrinogen concentrate (FC).Material/MethodsPPH patients’ demographic parameters, outcome variables, and laboratory finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Nonetheless, several other and older observational studies or reports from the UK, Japan and Turkey still maintain that fibrinogen supplementation is effective and beneficial. 14,[27][28][29][30][31] This is not surprising, as most patients in those studies presented very severe and advanced PPH, and much greater blood loss and much lower plasma fibrinogen concentrations (usually <1 g/l) than those reported in the randomised studies. Although the patients received numerous transfusions (including fresh frozen plasma, FFP) and were not compared with adequate control groups, the studies documented safety and established the usefulness of massive doses of fibrinogen (up to 8 g) to avoid FFP transfusion and fluid overload, and for rapid correction of very low fibrinogen levels.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nonetheless, several other and older observational studies or reports from the UK, Japan and Turkey still maintain that fibrinogen supplementation is effective and beneficial. 14,[27][28][29][30][31] This is not surprising, as most patients in those studies presented very severe and advanced PPH, and much greater blood loss and much lower plasma fibrinogen concentrations (usually <1 g/l) than those reported in the randomised studies. Although the patients received numerous transfusions (including fresh frozen plasma, FFP) and were not compared with adequate control groups, the studies documented safety and established the usefulness of massive doses of fibrinogen (up to 8 g) to avoid FFP transfusion and fluid overload, and for rapid correction of very low fibrinogen levels.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, three major randomised and well‐conducted controlled studies, FIB‐PPH, OBS2 and FIDEL, all found that early systematic fibrinogen replacement is not beneficial in the course of severe PPH management. Nonetheless, several other and older observational studies or reports from the UK, Japan and Turkey still maintain that fibrinogen supplementation is effective and beneficial 14,27–31 . This is not surprising, as most patients in those studies presented very severe and advanced PPH, and much greater blood loss and much lower plasma fibrinogen concentrations (usually <1 g/l) than those reported in the randomised studies.…”
Section: Discussionmentioning
confidence: 92%
“…In their study, Sahin et al [18] investigated the use of fibrinogen concentrates in obstetric hemorrhages. As a result of this study, it was observed that the use of appropriate fibrinogen reduces unnecessary blood product use, thus reducing the risk of volume overload and related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, three major randomized and well conducted controlled studies, FIB-PPH, OBS2 and FIDEL, all found that early fibrinogen replacement is not beneficial in the course of severe PPH management when a second line uterotonic agent is needed after prostaglandins and when plasma fibrinogen level is not known. Nonetheless, several other and older observational studies or reports from the UK, Japan, or Turkey still maintain that fibrinogen supplementation is effective and beneficial 14,[28][29][30][31][32] . This is not surprising, as most patients in those studies presented very severe and advanced PPH, and much greater blood loss and much lower plasma fibrinogen concentrations (usually < 1 g/L) than those reported in the randomized studies.…”
Section: Discussionmentioning
confidence: 99%